Encapsulation Fe-Nx combined with Co@C to construct efficient oxygen reduction catalysts with bimetallic sites and the application of Zn-air batteries. (December 2022) - Zhao, H.L.; Wu, S.; Liu, C.Y.; Yan, X.T.; Xu, X.; Fu, S.S.; Wang, Y.B.; Su, Q.; Wang, X.; Yang, Q.L.
Abstract: Highly active non-precious oxygen reduction (ORR) catalysts are expected to replace precious (Pt) metal oxygen reduction catalysts. An oxygen reduction catalyst (Co@C/Fe-NC) at the bimetallic active site was constructed by doping different types of metals before and after precursor synthesis. This doping method, which can effectively prevent the contact between different metal species. The synergistic effects produced by different metal species are more accurately studied. The prepared Co@C/Fe-NC catalysts have a dodecahedral shape, and the Co source catalyzes the formation of carbon nanotubes on the surface at high temperature. The metal sites are protected by the carbon layer, which can reduce the corrosion of electrolytes and metal agglomeration during circulation, and improve the catalytic activity and stability. The catalyst was tested to have a high onset potential (Eonset  = 1.02 V), half-wave potential (E1/2  = 0.86 V) and stability (negative shift 11 mV after 10, 000 cycles). When assembled into Zn-air batteries, it also exhibits excellent specific capacitance (769.81 mAh/g) and power density (100.4 mW/cm 2 ). The synergistic effect of Co@C and Fe-Nx makes it have significant ORR catalytic activity. Highlights: Rational doping strategies to construct well-defined bimetallic active sites. Synergistic action of bimetallic sites to enhance catalytic activity. Co@C/Fe-NC has excellent catalyst activity and stability. Zn-air batteries have excellent specific capacity, multiplier performance and long-term stability.